Singapore : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Singapore. (IMF Staff Country Reports; Country Report, 2022)
Singapore registered one of the most impressive recoveries from the pandemic, with economic output having surpassed pre-crisis levels at end-2021. This was spurred by the country's strong economic fundamentals, an impressive vaccination rollout, and the authorities' decisive policy responses. However, the recovery has been uneven with activities in tourism-related, consumer-facing and construction sectors remaining well below pre-pandemic levels. Inflation has risen rapidly due to higher food and energy, private transport, and housing prices, but inflation expectations remain well anchored. Risks to the outlook are tilted to the downside, arising mainly from the war in Ukraine and the related sanctions, the pandemic, China's growth slowdown, and monetary policy normalization in advanced economies.